2015
DOI: 10.3390/ijms16011644
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Retina by Mini-αA in NaIO3-Induced Retinal Pigment Epithelium Degeneration Mice

Abstract: Background: Studies have shown that mini-αA can protect retinal pigment epithelium (RPE) cells from apoptosis. However, no in vivo study concerning the anti-apoptotic function of mini-αA has been conducted yet. Methods: MTT assay, HE staining and TUNEL assay were used to assess levels of cells, and an animal model was established to examine the protective effects of mini-αA against NaIO3-induced RPE cell apoptosis. Western blot analysis and RT-qPCR were performed to explore the possible mechanism of mini-αA’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
(36 reference statements)
1
22
0
Order By: Relevance
“…7B). Our results is coherent to the 24-hour, 3.5 mM sodium iodate treatment, which LC3B-II expression is increased in ARPE-19 cells28. Similarly, 1 and 3-day hydrogen peroxide treatments also increase the autophagic activity in ARPE-19 cells, but reduces in the 14-day treatment19.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…7B). Our results is coherent to the 24-hour, 3.5 mM sodium iodate treatment, which LC3B-II expression is increased in ARPE-19 cells28. Similarly, 1 and 3-day hydrogen peroxide treatments also increase the autophagic activity in ARPE-19 cells, but reduces in the 14-day treatment19.…”
Section: Discussionsupporting
confidence: 88%
“…6). Increased expression of other unfolded protein response pathways, such as CHOP and XBP1, has also been reported in RPE cells with acute sodium iodate treatment28. These indicates that sodium iodate would induce ER stress in RPE cells.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The antiapoptotic and/or anti-inflammatory effects of recombinant human αA or αB crystallin were successfully demonstrated in several animal disease models such as experimental cataracts, experimental autoimmune encephalomyelitis (EAE), stroke, cardiac ischemia-reperfusion, optic neuropathy, experimental autoimmune uveitis (EAU), and retinal degeneration [74-79]. Work from the laboratories of Sharma and Clark have identified several short chain peptides of αA and αB crystallin that elicit chaperone properties [80-82].…”
Section: α-Crystallin and Its Constitutive Peptides As Therapeutic Momentioning
confidence: 99%
“…Theses adaptive activities provide a primary defense against undesirable outcomes of cellular stress, highlighting the possibility that αBC might be used therapeutically [29,30]. To date, the αBC induced protection has been demonstrated in various cell cultures including RPE cells, astrocytes, endothelial cells, and pericytes [31]. A pioneering therapeutic study showed that intravitreal delivered β-crystallins or γ-crystallins exerted nutritional effects on the RGCs after optic nerve crush.…”
Section: Discussionmentioning
confidence: 99%